High-Content Screening Identifies Vanilloids as a Novel Class of Inhibitors of NET Formation - Sondo, Elvira; Bertelli, Roberta; Pesce, Emanuela; Ghiggeri, Gian Marco; Pedemonte, Nicoletta (Frontiers in Immunology, 2019)
Neutrophils migrate to sites of infection where they phagocytose, degranulate, and/or, in the presence of appropriate stimuli, release decondensed chromatin strands (called neutrophil extracellular traps, NETs) for trapping and possibly killing microorganisms. NET formation is characterized by marked morphological cell changes, in particular within the nucleus. Lytic NET formation can be observed in neutrophils undergoing cell death, which is referred to as NETosis. Dysregulation of NET production and/or degradation can exert pathogenic effects, contributing to the pathogenesis of various diseases, including cystic fibrosis, autoimmune diseases and inflammatory conditions. By employing a phenotypic assay based on high-content imaging and analysis, we screened a library of biologically active compounds and identified vanilloids as a novel class of chemical compounds able to hinder NETosis induction and NET release. Vanilloids also markedly decrease cytosolic ROS production. The identification of novel vanilloid NET inhibitors, able to stop excessive or aberrant NET production might offer new therapeutic options for those disorders displaying NET overproduction.